Breast Cancer Self-concept at Prof. Dr. W. Z. Johannes Hospital Kupang - Ni Made Merlin; Antonius Rino Vanchapo (Alma Ata University Press, 2020)
ABSTRACTBreast cancer is the disease that many women fear the most. Breast cancer significantly affects the psychological states of the patients, including self-concept. Patients with breast cancer commonly experience a negative self-concept due to the disease and side effects of the treatment. However, problems of self-concept among patients with breast cancer are rarely investigated by nurses. Furthermore, no measurement tool specifically measures the self-concept of breast cancer patients. The purpose of this study was to examine the validity and reliability of the self-concept questionnaire. This study used a case study research design to measure the self-concept of breast cancer patients using a newly developed questionnaire, namely the Merlin Breast Cancer Self-Concept Questionnaire. This questionnaire will be tested on breast cancer patients undergoing treatment in the hospital. The result showed a Cronbach’s alpha value of 0.909 for the validity and 0.500-0.790 for the reliability of the instrument. Merlin Breast Cancer Self-Concept Questionnaire was evident to be a valid and reliable instrument to measure self-concept among breast cancer patients. This questionnaire is feasible for use to measure self-concept among breast cancer patients. Implication for practice: This questionnaire will greatly help the clinic nurse in measuring the patient's self concept. Psychological problems especially self-concept can be examined to improve